The Effectiveness Of A Mixed Economic Model In Controlling The Financial System In 7 Emerging Market Countries - Audre Aprillia; Winsi Fadiah Putri; Nurul Syahfia; Rusiadi Rusiadi; Diwayana Putri Nasution; Bakhtiar Efendi; Lia Nazliana Nasution (International Journal of Economics, Commerce, and Management, 2024)
This research aims to analyze the effectiveness of the mixed economic model in controlling financial system stability in 7 emerging market countries. Where the monetary policy variables are the money supply and interest rates. Then the microprudential variables are Return On Equity and Return On Assets, the macroprudential variables are Capital Adequacy Ratio and Non Performing Loans. The financial system stability variables are the inflation level and exchange rate. The data analysis model in this research is the Simultaneous model. This research uses secondary data or time series, namely from 2019 to 2023. This analysis is significant for controlling the financial system by ensuring the data meets normality assumptions through the Jarque-Bera test, which allows for more precise financial planning and risk management decisions. The absence of autocorrelation effects, as proven in the residual test, also strengthens the reliability of the model in understanding market trends. The Two-Stage Least Squares method in simultaneous regression analysis provides in-depth insight into the relationship between economic variables such as the inflation rate and the exchange rate, supporting effective economic policy making. Understanding the elasticity of key variables to the inflation rate and exchange rate is also important for optimizing risk control strategies and financial resource allocation.